Reimagining the Law of Delict in Sri Lanka: The need for a coherent common law tradition - Ahamed, V.K. (University of Colombo, 2025)
Sri Lanka’s law of delict, though rooted in Roman Dutch law, has evolved under the influence of English and South African authorities as well as local traditions. This layered development has produced a fragmented and uncertain body of doctrine, often marked by inconsistency in the reception and application of foreign sources. A coherent and locally grounded framework is therefore needed to maintain clarity and predictability in civil justice. This paper argues for a principled approach that reflects Sri Lankan values and institutional realities, supported by a consistent judicial method. Using Aquilian liability as its focus, it adopts a qualitative doctrinal method with selective comparative analysis of English and South African sources. It contrasts the restrictive approach in Priyani Soyza v Arsecularatne with the more progressive Karunanayake v Mannapperuma, which affirmed the adaptability of the lex Aquilia. These cases highlight both the potential and the limits of judicial development in the absence of structured doctrine. The study proposes a framework organized around the elements of wrongful conduct, fault, causation, and damage, with defines and justifications clearly defined. Fault remains the general basis of liability, ...
Keywords: Delict; Aquilian action; Roman-Dutch law; English law; Judicial borrowing; Indigenous common law